(untitled) (Research, Society and Development, 2023)
The SARS-CoV-2 virus, known worldwide as Coronavirus or Covid-19, named because of the shape and class of the virus. It is possible to observe that there are numerous manifestations in relation to covid, going from distinct to interdependent perspectives, it is necessary to analyze the common clinical manifestations. Objective: to understand the sequelae presented by patients affected by the SARS-CoV-2 virus. Methodology: This is an integrative literature review article. Results: This work was carried out with 15 carefully selected articles that answered the guiding question. Conclusion: it is concluded that pulmonary changes are among the most common sequelae of cases of Covid-19, being with the cough, fatigue and changes in imaging tests, it is still not known the period of installation is possible return of these sequelae. Neurological changes are also present in part of the population, the most common being the loss and decrease in taste and taste sensation, it is not clear in the literature the period of post covid sequelae.